Concomitant Intraspinal and Retroperitoneal Hemorrhage Caused by an Aneurysm on the Celiac Artery: A Case Report - Vermeulen, Katrien; Schwagten, Veerle; Menovsky, Tomas (Journal of Neurological Surgery Reports, 2015)
Spontaneous spinal hemorrhage is a rare condition. We present a case in which the diagnosis was complicated by a concomitant intra-abdominal hemorrhage. The patient, taking coumarins, presented with acute back pain and abdominal pain and progressive paresis of the lower limbs. Computed tomography angiography of the abdomen showed an intra-abdominal hemorrhage and an aneurysm of the celiac trunk. MR (magnetic resonance) imaging of the spine revealed a combined subdural and epidural hemorrhage from C1 to L1. Both sites were treated conservatively. After 6 months the patient regained strength in both legs with some persistent loss of strength in the left leg. Follow-up MR imaging showed complete resolution of the spinal hemorrhage. The celiac artery aneurysm was treated conservatively. We suggest that the rupture of the celiac artery aneurysm caused increased intra-abdominal pressure leading to spinal hemorrhage. Emergency staff should be aware of the possibility of two rare but concomitant conditions.
Keywords: spinal hemorrhage; coumarins; celiac trunk aneurysm; paresis; abdominal hemorrhage